Effectiveness of low-dose and standard-dose tamsulosin in the treatment of distal ureteric stones: A randomized controlled study - Bannakij Lojanapiwat (2018)
Low-dose (0.2 mg/day) and standard-dose (0.4 mg/day) tamsulosin were studied in a randomized controlled trial of 75 outpatients with distal ureteroliths in Thailand. Group 1 (n = 25; control) received oral sodium diclofenac 50 mg twice a day for 10 days; group 2 (n = 25) received oral sodium diclofenac 50 mg twice a day for 10 days, with oral tamsulosin 0.2 mg once a day up to 28 days; and group 3 (n = 25) received oral sodium diclofenac 50 mg twice a day for 10 days, with oral tamsulosin 0.4 mg once a day up to 28 days. For groups 1, 2 and 3, respectively, the expulsion rates were 4%, 40% and 68% (significantly different for group 1 vs group 2, and for group 1 vs group 3) and mean expulsion times were 23.00, 9.30 and 10.76 days. Both doses of tamsulosin increased stone expulsion rate and decreased expulsion time in comparison with the control, and have been shown to be safe and effective in Asian patients. Copyright © 2008 Field House Publishing LLP.